THE RELEVANCE OF IBNU TAIMIYAH’S WAGE CONCEPT FOR CONSTRUCTION WORKERS IN PANGEREMAN VILLAGE - Lailatul Maufiroh; Fadllan (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2022)
ABSTRACT The concept of wages according to Ibn Taimiyah is the level of wages that must be given to workers. So that, they can live properly in the midst of society. Equivalent wages are remuneration in the form of money and so on which are paid to repay services. The aimed of this research is to identify the relevance of Ibnu Taimiyah’s wage concept for construction workers in Pangereman Village, Sampang Madura. This research is conducted using qualitative research method, which the data are from the literatures related with the wage concept of Ibnu Taimiyah perspective, then it is completed by interview. The obtained data becomes the relevant material with the concept offered by Ibn Taimiyah. The results of this research describe that the head of construction workers implements the concept of wages from Ibn Taimiyah's perspective, namely the concept of fair and honest wages. Employment agreements are made at the beginning and remuneration is carried out at the end. The head construction workers adjusts the quality and quantity of the performance of the workers. The better their performance quality, the higher the wages level they will get, and the more days they work, the more wages they will get. ABSTRAK Konsep upah menurut Ibnu Taimiyah adalah tingkat upah yang harus diberikan kepada pekerja agar dapat hidup layak di tengah-tengah masyarakat. Upah yang setara adalah balas jasa dalam bentuk uang dan sebagainya yang dibayarkan untuk membayar kinerjanya. Tujuan dari penelitian ini adalah untuk mengidentifikasi relevansi konsep upah yang ditawarkan oleh Ibn Taimiyah dengan implementasi pengupahan buruh bangunan di Desa Pangereman, Sampang Madura . Penelitian ini mengadopsi jenis penelitian kualitatif, dimana datanya diperoleh dari kajian-kajian terkait pengupahan perspektif Ibnu Taimiyah, kemudian dilengkapi dengan hasil interview. Data yang diperoleh dijadikan bahan yang direlevansikan dengan pemikiran Ibn Taimiyah. Hasil penelitian ini menjelaskan bahwa kepala buruh bangunan menerapkan konsep pengupahan dari sudut pandang Ibnu Taimiyah, yaitu konsep pengupahan yang adil dan jujur. Perjanjian kerja dibuat di awal dan remunerasi dilakukan di akhir. Kepala pekerja konstruksi menyesuaikan kualitas dan kuantitas kinerja pekerja. Semakin baik kualitas kinerja mereka, semakin tinggi tingkat upah yang akan mereka dapatkan, dan semakin banyak hari mereka bekerja, semakin banyak upah yang akan mereka dapatkan.